2008
DOI: 10.1093/ajcn/87.5.1384
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate intake, glycemic index, glycemic load, and risk of postmenopausal breast cancer in a prospective study of French women

Abstract: Rapidly absorbed carbohydrates are associated with postmenopausal breast cancer risk among overweight women and women with large waist circumference. Carbohydrate intake may also be associated with estrogen receptor-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 39 publications
4
91
1
1
Order By: Relevance
“…This was agreed by another cohort of Nurses' Health Study which found there was no significant association between carbohydrate intake and breast cancer risk among premenopausal women (Holmes et al, 2004). Studies among postmenopausal women were more intensively conducted but majority of them found no significant association between carbohydrate intake and breast cancer risk at an intake of 50% to 55% of energy (Holmes et al, 2004;Nielsen et al, 2005;Lajous et al, 2008;Larsson et al, 2009;Shikany et al, 2011). However, at a higher intake of carbohydrate achieving 82% of energy contribution (344 g/day), a prospective study in China found a significant two-fold increased risk of breast cancer among premenopausal (HR=2:01; 95%CI: 1.26 to 3.19), but not postmenopausal (Wen et al, 2009).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This was agreed by another cohort of Nurses' Health Study which found there was no significant association between carbohydrate intake and breast cancer risk among premenopausal women (Holmes et al, 2004). Studies among postmenopausal women were more intensively conducted but majority of them found no significant association between carbohydrate intake and breast cancer risk at an intake of 50% to 55% of energy (Holmes et al, 2004;Nielsen et al, 2005;Lajous et al, 2008;Larsson et al, 2009;Shikany et al, 2011). However, at a higher intake of carbohydrate achieving 82% of energy contribution (344 g/day), a prospective study in China found a significant two-fold increased risk of breast cancer among premenopausal (HR=2:01; 95%CI: 1.26 to 3.19), but not postmenopausal (Wen et al, 2009).…”
Section: Discussionmentioning
confidence: 79%
“…Concurrently, there have been striking changes in mortality rates of breast cancer among other cancers which lagged around 10 years from the beginning of the nutrition transition towards a westernized diet in selected geographical location in East Asia (Zhang et al, 2012). In the past decade, dietary carbohydrate, fiber and sugar has gained much attention in relation towards breast cancer risk according to menopausal status, but studies have been limited in developed countries (Cho et al, 2003;Holmes et al, 2004;Romieu et al, 2004;Mattisson et al, 2004;Nielsen et al, 2005;Giles et al, 2006;Cade et al, 2007;Lajous et al, 2008;Suzuki et al, 2008;Larsson et al, 2009;Wen et al, 2009;Park et al, 2009;Shikany et al, 2011;Zaineddin et al, 2012;Ferrari et al, 2013;Li et al, 2013;Woo et al, 2013). A few studies have appeared from South-East Asia and Eastern Europe (Kruk and Marchlewicz, 2013;Sangrajrang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it might be hypothesized that its effects differ according to the time of day at which the beverage is drunk, thereby potentially affecting breast cancer risk (26) . However, our data did not confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies categorised intake by quartiles (McCann et al, 2007;Sieri et al, 2007;Lajous et al, 2008) or quintiles (Augustin et al, 2001;Cho et al, 2003;Jonas et al, 2003;Frazier et al, 2004;Higginbotham et al, 2004;Holmes et al, 2004;Lajous et al, 2005;Silvera et al, 2005). Two studies could not be included in meta-analyses, as GI/GL intakes were only examined as continuous variables (Nielsen et al, 2005;Giles et al, 2006), and another study was excluded, as it did not present results separately by menopausal status (Levi et al, 2002).…”
Section: Methodsmentioning
confidence: 99%